ANALISIS POTENSI PEMANFAATAN TEKNOLOGI INTERNET DALAM MENUNJANG KEHIDUPAN SOSIAL EKONOMI MASYARAKAT KABUPATEN MIMIKA - Alfian Delfiantrisno; Siska Sroyer (JURNAL KRITIS (Kebijakan, Riset, dan Inovasi), 2020)
The purpose of this study was to determine the potential use of internet technology in supporting the socio-economic life of the people of Mimika Regency. The method used is descriptive method. Data collection instruments used to obtain data in this study were using questionnaire techniques, literature studies and observation.The analysis instrument used in this study is the SWOT analysis. The results of this study indicate that:the community in Mimika Regency has the potential to utilize internet technology to support the socio-economic community. The strategies that can be used to maximize the existing potential are:1) Businesses can target markets outside Kab. Mimika; 2) Increase investment in the digital economy sector; 3) The government can advance telecommunications infrastructure in underdeveloped region; 4) Educating the public regarding the potential use of internet technology.